Antioxidant, Anti-Inflammatory and Anti-Diabetic Activities of Tectona grandis Methanolic Extracts, Fractions, and Isolated Compounds - Mei Han; Fengxian Yang; Kun Zhang; Jiyan Ni; Xia Zhao; Xuelin Chen; Zhennan Zhang; Hanlei Wang; Jing Lu; Yumei Zhang (MDPI AG, 2023)
Tectona grandis is a traditional Dai medicine plant belonging to the Lamiaceae family, which can be used to treat malaria, inflammation, diabetes, liver disease, bronchitis, tumors, cholelithiasis, jaundice, skin disease and as an anti-helminthic. To find more novel therapeutic agents contained in this medicinal plant, the antioxidant, anti-inflammatory and anti-diabetic activities of T. grandis methanolic extract, fractions and compounds were evaluated. In this study, 26 compounds were isolated from the leaves and branches of T. grandis. Their structures were identified based on extensive spectral experiments, including NMR, ESI-MS and comparison with published spectral data. Among them, compounds 1-2, 4-6, 9-14 and 16-22 were reported for the first time for this plant. The antioxidant activity screening results showed that compounds 5, 15 and 23 had potent antioxidant capacities, with SC50 values from 0.32 to 9.92 µmol/L, 0.92 to 1.10 mmol Trolox/L and 1.02 to 1.22 mmol Trolox/L for DPPH, ABTS and FRAP, respectively. In addition, their anti-inflammatory effects were investigated by releasing TNF-α, IL-1β and IL-6 through the use of mouse monocytic macrophages (RAW 264.7). Compounds 1, 13, 18 and 23 had the effects of reducing the expression of inflammatory factors. Compounds 13 and 18 were reported for the first time for their anti-inflammatory activities. Furthermore, the methanolic extract (ME), petroleum ether extract (PEE) and EtOAc extract (EAE) of T. grandis showed significant glucose uptake activities; compounds 21 and 23 significantly promoted glucose uptake of 3T3-L1 adipocytes at 40 µM. Meanwhile, compounds 4, 5 and 7 showed significant inhibitory activities against α-glucosidase, with IC50 values of 14.16 ± 0.34 µmol/L, 19.29 ± 0.26 µmol/L and 3.04 ± 0.08 µmol/L, respectively. Compounds 4 and 5 were reported for the first time for their α-glucosidase inhibitory activities. Our investigation explored the possible therapeutic material basis of T. grandis to prevent oxidative stress and related diseases, especially inflammation and diabetes.